A Simple and Sensitive Electrochemical Sensor for Chloramphenicol Detection in Pharmaceutical Samples. Issue 8 (8th May 2020) - Kaewnu, Krittapas; Promsuwan, Kiattisak; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Abstract : This work presents a square-wave adsorptive stripping voltammetric sensor for the determination of chloramphenicol (CAP) using a glassy carbon electrode modified with branch-like poly (eriochrome black T) film (P(EBT)/GCE). Branch-like P(EBT) film on the GCE was prepared by electropolymerization using cyclic voltammetry. The morphology of the P(EBT)/GCE was characterized by scanning electron microscopy. The concentration of eriochrome black T monomer and the number of electropolymerization cycles used in the fabrication process were optimized. Operational conditions, such as accumulation potential and accumulation time were also optimized. Sensitive determinations were achieved from controlled adsorption at the P(EBT)/GCE. The P(EBT)/GCE exhibited two linear ranges, 0.01 to 0.10 and 0.10 to 4.0 μ mol L −1, with high sensitivity (5.2 μ A μ M −1 ). The limit of detection and quantitation were 3 and 11 nmol L −1, respectively. Repeatability (RSD < 2.7%, n = 18), reproducibility (RSD < 2.8%, n = 6) and anti-interference were good. The sensor determined CAP in eye drops and ointment with recoveries between 96 ± 3% and 102 ± 1% (n = 3).